2012
DOI: 10.3171/2012.6.spine111054
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid dynamic stabilization: a biomechanical assessment of adjacent and supraadjacent levels of the lumbar spine

Abstract: Object The object of this study was to evaluate the effect of hybrid dynamic stabilization on adjacent levels of the lumbar spine. Methods Seven human spine specimens from T-12 to the sacrum were used. The following conditions were implemented: 1) intact spine; 2) fusion of L4–5 with bilateral pedicle screws and titanium rods; and 3) supplementation of the L4–5 fusion with pedicle screw dynamic stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…4 Our biomechanical study using finite element analysis also revealed stiffness resulting from the Dynesys system which is the same as that from rigid fixation. 10 In contrast to the results of Mageswaran et al, Durani et al reported that a dynamic stabilization system could reduce the hypermobility caused by extended arthrodesis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…4 Our biomechanical study using finite element analysis also revealed stiffness resulting from the Dynesys system which is the same as that from rigid fixation. 10 In contrast to the results of Mageswaran et al, Durani et al reported that a dynamic stabilization system could reduce the hypermobility caused by extended arthrodesis.…”
Section: Discussionmentioning
confidence: 60%
“…3 Hybrid surgery is not to prevent further degeneration of the asymptomatic adjacent segment but is used to replace fusion when treating symptomatic, degenerated adjacent segments. 4 Thus, a retrospective comparative study was done in patients with hybrid surgery or pure fusion surgery for lumbosacral degenerative disease involving two-segments.…”
Section: Introductionmentioning
confidence: 99%
“…29,35 It is unique in its ability to efficiently combine both load control and displacement control for testing of multisegmental specimens. It also provides the flexibility to control both the loading and boundary conditions, desired for conducting biomechanical tests.…”
Section: Discussionmentioning
confidence: 99%
“…The mounting procedure and robotic test system have been described in detail in previous studies. 28,29,39 For this study, the robot was programmed to apply 3 continuous loading and unloading cycles of applied moment along each primary axis of motion to simulate flexion-extension (FE), lateral bending (LB), and axial rotation (AR). The specimens were preconditioned to eliminate any viscoelastic effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation